1985
DOI: 10.1029/jb090ib12p10310
|View full text |Cite
|
Sign up to set email alerts
|

Strain accumulation in the Rocky Mountain states

Abstract: Strain accumulation in trilateration networks in Montana, Utah, and New Mexico has been measured for over a decade. The network in New Mexico spans the Rio Grande rift near Socorro. The absence of any observed strain accumulation in that network places an upper limit (2 standard deviations) of 3 mm/a on east‐west spreading across the 100‐km‐wide rift. The network in Utah spans the Wasatch fault near Ogden. Although the 1972–1984 average rate of strain accumulation in that network is not significant at a 2‐stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…On the basis of relocated teleseismically recorded aftershocks for the Hebgen Lake earthquake,Dewey et al [1972, p. 886] suggest that "the fault surface of the main shock at depth extended a considerable distance east and west of the surface fault scarps. "Savage et al [1985] reached this same conclusion from analysis of horizontal strain measurements.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…On the basis of relocated teleseismically recorded aftershocks for the Hebgen Lake earthquake,Dewey et al [1972, p. 886] suggest that "the fault surface of the main shock at depth extended a considerable distance east and west of the surface fault scarps. "Savage et al [1985] reached this same conclusion from analysis of horizontal strain measurements.…”
supporting
confidence: 56%
“…Additional evidence for postearthquake deformation in the Hcbgen Lake area was reported by Prescott et al [1979] and Savage et al [1985] on the basis of trilateration surveys conducted by the U.S. Geological Survey (USGS) since 1973. These measurements indicate uniaxial extension perpendicular to the 1959 rupture trace at a rate of 0.28 + 0.02 #strain/yr.…”
mentioning
confidence: 79%
“…2) has, however, been attributed to water pumping near Albuquerque (Reilinger et al 1980). While horizontal strain rates of this magnitude were recorded in the vicinity of Socorro during a 1972-1984 trilateration survey (Savage et al 1985), the inferred strains revealed no systematic temporal pattern, and in fact changed their sign during the period of observation. the preferred model of Larsen et al 1986) would imply a surface contraction in these areas giving rise to a strain rate of the order of (subsidence rate)/ (source depth).…”
Section: Origin Of Uplift: Continual Magma Injection or In Situ Melting?mentioning
confidence: 92%
“…Note that the spherical deflation sources in the middle crust beneath Belen and Socorro (i.e. The absence of a systematic strain accumulation in the trilateration data of Savage et al (1985) argues against volume changes in the middle crust below the Rio Grande rift. That is, for a subsidence rate of several millimetres per year and a source depth of 19 km, the corresponding strain rate is O(10 x7 yr x1 ).…”
Section: Origin Of Uplift: Continual Magma Injection or In Situ Melting?mentioning
confidence: 99%
“…Grande (Savage et al 1985), Baikal (Calais et al 1998), and the Rhine Graben (Ahorner 1983). Elsewhere, opening rates are based on magnetic lineations in the Woodlark Rift (Taylor et al 1995) and the Red Sea-Gulf of Suez.…”
Section: Seismicity In Riftsmentioning
confidence: 99%